EFFICIENCY OF UPLAND RICE IN DIFFERENT KINDS OF FURROW OPENING IMPLEMENTS SOIL AND NITROGEN FERTILIZATION - BONINI, Carolina dos Santos Batista; ALVES, Marlene Cristina; NASCIMENTO, Vagner do; ARF, Orivaldo; COSTA, Nídia Raquel (Revista Brasileira de Engenharia de Biossistemas, 2010)
Rice is the staple diet of millions of people in most countries of the world. In recent years direct seeding on the remains of previous crops is gaining expression in the central region of Brazil. In this sense this work was developed which aimed to evaluate the effect of two mechanisms for distributing the fertilizer at sowing and to investigate the influence of different doses of nitrogen on the yield of upland rice grown under direct seeding. The area is being managed with no-till since 1999, so 6 years ago. The study was conducted in the municipality of Selvíria-MS on a Oxisol, originally under cerrado vegetation. The experimental design was a randomized complete block with 12 treatments consisting of the combination of two mechanisms for distributing fertilizer at sowing (double disc and chisel) and different doses of nitrogen (0, 25, 50, 75, 100 and 125 kg ha -1) in the tillage system, with 4 blocks. Were evaluated: the milling yield (ingenuity, whole and broken), hectoliter mass, plant height and content of N. According to the obtained results it can be concluded that there was a positive influence on different mechanisms and doses used. The application of nitrogen interfered in some agronomic characteristics and did not affect yield components of rice mill. Use chisel resulted in taller plants and more nitrogen in the leaves. Increasing doses of N influenced the increase of hectoliter mass and plant height.